The Investigation of the Ardales Cave, Spain – 3D Documentation, Topographic Analyses, and Lighting Simulations based on Terrestrial Laser Scanning. Issue 2 (15th July 2015) - Hoffmeister, Dirk; Zellmann, Stefan; Pastoors, Andreas; Kehl, Martin; Cantalejo, Pedro; Ramos, José; Weniger, Gerd‐Christian; Bareth, Georg
Abstract: This contribution shows the application of terrestrial laser scanning in an integrative approach for the documentation and analyses of the Ardales Cave, southern Spain, which is in many respects an important geoarchaeological site. For the survey of the cave, a combination of the Riegl LMS Z420i laser scanner with a real‐time kinematic global positioning system (RTK‐GPS) from Topcon and further tachymetric measurements were used. The achieved three‐dimensional (3D) model of the cave and the surrounding hill documents the current topography and dimensions of the cave. Additional geoarchaeological data were successfully integrated in a 3D geographical information system (GIS) database and high‐resolution records of a structured‐light scanner were combined with the 3D model of the cave. The 3D model is further used for the estimation of the ceiling thickness that reveals areas for additional entrances. Lighting simulations based on path tracing were conducted for the determination of areas that are reached by natural direct or indirect light. In this case, the weight and size of the instrument was a logistic constraint to reach certain areas and to achieve a complete model of the cave. Overall, the method is feasible for the documentation of this cave and the investigations based on the derived 3D models. Copyright © 2015 John Wiley & Sons, Ltd.